Profesionalisme Guru dalam Mengimplementasikan Teknologi Informasi dan Komunikasi di Kabupaten Nganjuk - Imam Abdul Syukur (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2014)
This study aims to: 1) investigate perception of teachers of elementary school, junior secondary school, senior secondary school, and vocational school toward the teachers professionalism in implementing Information and Communication Technology to improve the quality of learning; 2) investigate opinion of students in the teachers professionalism in elementary school, junior high school, senior high school and vocational school toward the teachers professionalism in implementing Information and Communication Technology; 3) investigate are the things that are still a constraint of teachers in implementing Information and Communication Technology to improve the quality of learning. The population is all teachers in elementary school, junior high school, senior high school and vocational school in Nganjuk District which sample taken by simple random sampling. Data collection techniques used questionnaire by the Likert scale. The results of this study indicate that: 1) teachers of elementary school, junior high school, senior high school and vocational school majority (52.75%) stated that they rarely use the laptop for teaching learning process; 2) student of elementary school, junior high school, senior high school and vocational school majority (62.15%) stated that Information and Communication Technology teachers rarely use Information and Communication Technology in teaching learning; and 3) constraints majority of teachers of elementary school, junior high school dan senior high school (34.95%) in implementing Information and Communication Technology for teaching learning is the lack of mastery of Information and Communication Technology, whereas for vocational teachers (10.03%) is the lack of facilities and infrastructure support.ABSTRAK Penelitian ini bertujuan untuk: 1) mengkaji persepsi guru Sekolah Dasar, SekolahMenengah Pertama, Sekolah Menengah Atas dan Sekolah Menengah Kejuruan terhadap profesionalisme guru dalam mengimplementasikan Teknologi Informasi dan Komunikasi untuk meningkatkan kualitas pembelajaran; 2) mengkaji pendapat siswa Sekolah Dasar, Sekolah Menengah Pertama, Sekolah Menengah Atas dan Sekolah Menengah Kejuruan terhadap profesionalisme guru dalam mengimplementasikan Teknologi Informasi dan Komunikasi; 3) mengkaji kendala-kendala guru dalam mengimplementasikan Teknologi Informasi dan Komunikasi untuk meningkatkan kualitas pembelajaran. Populasi penelitian meliputi seluruh guru Sekolah Dasar, Sekolah Menengah Pertama, Sekolah Menengah Atas dan Sekolah Menengah Kejuruan di Kabupaten Nganjuk dengan penarikan sampel secara simple random sampling. Teknik pengumpulan data menggunakan angket dengan skala Likert. Hasil penelitian menunjukkan bahwa: 1) 52,75% guru Sekolah Dasar, Sekolah Menengah Pertama, Sekolah Menengah Atas dan Sekolah Menengah Kejuruan menyatakan jarang menggunakan laptop untuk pembelajaran; 2) 62,15% Teknologi Informasi dan Komunikasi siswa Sekolah Dasar, Sekolah Menengah Pertama, Sekolah Menengah Atas dan Sekolah Menengah Kejuruan menyatakan bahwa guru jarang menggunakan Teknologi Informasi dan Komunikasi dalam pembelajaran; dan 3) 34,95% guru Sekolah Dasar, Sekolah Menengah Pertama, dan Sekolah Menengah Atas kurang menguasai Teknologi Informasi dan Komunikasi, sedangkan 10,03% guru Sekolah Menengah Kejuruan menyatakan bahwa sarana dan prasarana yang ada kurang mendukung dalam pembelajaran.